Tuning the electronic, mechanical, thermal, and optical properties of tetrahexcarbon via hydrogenation - Kilic, Mehmet Emin; Lee, Kwang-Ryeol (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Recently, Tetrahexcarbon (TH-carbon), a new two-dimensional(2D) carbon allotrope, has been identified with an intrinsic direct bandgap, which makes it promising for practical applications in optoelectronic devices. Using first-principles calculations, we examined the possibility of manipulating the physical and chemical properties of TH-carbon sheet by controlled hydrogenation. We systematically studied pristine TH-carbon and its hydrogenated derivatives with various configurations such as single- and double-sided hydrogenation. Our study revealed their stability in energetic, dynamic, thermal, and mechanical aspects. Depending on the hydrogen coverage and configurations, we observed the tunability of the phononic and electronic bandgap, and the direct-indirect-direct bandgap transitions. These results suggest the plausibility of modulating its electronic properties by hydrogenation. The heat transport in TH-carbon is anisotropic. A significant decrease in thermal conductivity was observed in the fully hydrogenated TH-carbon. The thermal conductivity in TH-carbon can be controlled by the sp(3) C-H low conduction domains. A notable increase in specific heat capacity was observed in hydrogenated derivatives of TH-carbon, which would make them useful in nanoscale engineering of thermal transport. The hydrogenation was found to reduce the in-plane stiffness and Young's modulus, but increase the ultimate strength. These findings would provide important guidelines for practical applications of TH-carbon. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: PENTA-GRAPHENE; ULTRASOFT PSEUDOPOTENTIALS; REVERSIBLE HYDROGENATION; 2-DIMENSIONAL MATERIALS; BAND-GAP; CARBON; DYNAMICS; 1ST-PRINCIPLES; NANOSHEETS; SEMICONDUCTORS